SD-OCT-histopathologic correlation in Schnabel’s cavernous optic nerve atrophy - Weber, C.; Mercieca, K.; Weller, Julia; Bulirsch, L. M.; Ach, T.; Holz, F. G.; Loeffler, K. U.; Herwig-Carl, M. C. (Eye, 2025)
Background: Until now, Schnabel’s cavernous optic nerve atrophy (SCONA) has solely been a histopathological diagnosis exhibiting variable degrees of optic nerve (ON) atrophy with characteristic cavernous spaces filled with acid mucopolysaccharides. We report the first correlation of histopathologic findings with spectral domain-optical coherence tomography (SD-OCT) imaging in SCONA. Methods: We examined the eye of an index patient with histopathologically identified SCONA who had undergone multimodal imaging before enucleation for iris ring melanoma. The extent of SCONA in the index patient and three other enucleated eyes with SCONA were determined histopathologically. The histopathological findings of our index patient were correlated with in vivo SD-OCT images before enucleation and compared to representative images from eyes with a normal versus glaucomatous optic disc. Results: Histopathologic examination of our index patient showed a pre- and intralaminar extension of SCONA. Atrophy of the inner retinal layers was observed corresponding to the extent of SCONA. Correlation with SD-OCT showed small intralaminar hyporeflective pseudocysts which were detected in multiple scans corresponding to the histologically affected areas. These changes were neither visible in scans of patients with glaucomatous atrophy nor those with a normal ON. Conclusions: We present the first correlation of clinical and pathological findings in SCONA and were able to identify distinct SD-OCT characteristics for this condition. These findings may help to detect SCONA in vivo and to study this rare entity clinically with regard to its clinical course, risk factors, and pathogenesis. However, more cases of SCONA are needed to confirm our findings.
CRIS-Team Scopus Importer:2025-02-17